Dynamics of renin-angiotensin-aldosteron system and lipid profile in hypertensive hypothyrosis patients during the process of thyroid function compensation - P. Kh. Dzhanashiya (Российский кардиологический журнал, 2004)
The study was devoted to dynamics of plasma renin, aldosteron, and lipid profile in patients with primary hypothyrosis and arterial hypertension during hormone replacement therapy and thyroid function compensation. In the phase of hypothyrosis compensation, a significant increase in plasma renin and aldosteron concentration was registered. In subcompensation phase, triglyceride levels were reduced in hypothyrosis without arterial hypertension (AH) in anamnesis; in compensation phase, total cholesterol and low-density lipoprotein cholesterol concentrations were decreased. Among patients with hypothyrosis and AH in anamnesis, total cholesterol and triglyceride levels were reduced in compensation phase, but not normalized.